Differential value of eosinophil count in acute coronary syndrome among elderly patients. (9th April 2021) - Sincer, Isa; Gunes, Yilmaz; Mansiroglu, Asli Kurtar; Aktas, Gulali
Abstract: We aimed to search eosinophil (EOS) counts in elderly acute coronary syndrome (ACS) subjects and to investigate its value for discrimation between unstable angina pectoris (UAP) and myocardial infarction (MI) [non-ST elevation MI (NSTEMI) or ST elevation MI (STEMI)]. The patients were divided into three groups regarding the diagnosis: patients with UAP (63), with NSTEMI (154), and with STEMI (73). General characteristics such as gender, age, systolic and diastolic blood pressure were obtained from patients' files. Complete blood count and biochemical parameters were measured before coronary angiography. EOS was found significantly higher in UAP (0.134 (0.002–0.746) u/mm 3 ) compared to NSTEMI (0.085(0.001–0.601) u/mm 3 ) and STEMI (0.020(0.001–0.479) u/mm 3 ) groups. Kruskal–Wallis test with Bonferroni-corrected Mann–Whitney U-test revealed that EOS count was significantly different between UAP and NSTEMI ( p < .001), UAP and STEMI ( p < .001) and NSTEMI and STEMI ( p < .001) groups. A receiver operating curve (ROC) analysis revealed that a cut-off >0.083 u/mm 3 EOS value had a sensitivity of 79% and specificity of 57% for determination of ACS as UAP (AUC = 0.686, 95% CI, 0.617–0.755). In the present study, we detected an inverse relationship between the number of blood eosinophil count and the severity of ACS subgroups in elderly patients with higher counts in UAP than MI groups.